Design of an array of piezoresistive airflow sensors based on pressure loading mode for simultaneous detection of airflow velocity and direction - Chen, Jinyan; Liu, Pengzhan; Hu, Jie; Yang, Jianlin; Chen, Chao (Review of scientific instruments, 2022)
As an irreplaceable element for obtaining airflow information in many engineering scenarios, airflow sensors have gained increasing attention across the fields of aerospace engineering, environmental engineering, sustainable energy exploitation, meteorology research, and so on. As one of the mainstream airflow sensing principles, piezoresistive airflow velocity sensors have experienced rapid growth over the years, while effective vector airflow sensors with the ability of detecting both airflow velocity and direction based on the piezoresistive principle are scarce. Here, on the basis of our developed piezoresistive airflow velocity sensors based on pressure loading mode, we design an array of these sensors and propose a corresponding explicit algorithm for simultaneous detection of airflow velocity and direction. This sensor array configuration enables an automatic recognition function of the quadrant of incoming airflow, which can significantly simplify the reverse calculation of airflow information compared with conventional vector airflow sensors. The experimental results demonstrate the decent performance of this sensor array for identifying both airflow velocity and direction. This study not only fills the gap between our developed airflow velocity sensor and the ability of detecting airflow direction but also presents a simple and universal array-based strategy for vector airflow sensing, which could be widely applied in airflow sensors based on other principles.